Influencing Factors on the Sports Business: United Nations Sustainable Development Goals Approach through Championship Sports - Makki Mohmmed Safi; Rasool Nazari; Hassanin Abdul Wahed Abbas; Khosro Jalai Dehkordi (Sports Business Journal)
Purpose: Sports business development is a tool to facilitate sustainable development goals. The research aimed to identify the factors affecting the development of championship sports and their role in promoting the seventeen sustainable development goals.Methodology: The qualitative research was grounded in an interpretive paradigm and utilized thematic analysis. Using a targeted method, in-depth interviews were conducted with seventeen sports organizations, including universities, the Ministry of Sports and Youth, and federations. Analysis was carried out using Castleberry and Nolen's (2018) five-step model, which involves compiling, disassembling, reassembling, interpreting, and concluding. The quality of the findings was validated by calculating the percentage of coding agreement and by establishing the codes through three interview participants.Findings: Challenges include infrastructural and physical, general, programmatic, financial, economic and business, and attitudinal-cognitive. Basic measures include manpower supply, talent acquisition, culture building, education, and research. Advanced measures include emulating prosperous countries, providing sustainable financial, economic, and business resources, environmental solutions, and creating a professional labor market. Supportive factors include human and media support, which are identified as the study's main sub-themes. The development of championship sports can significantly impact the facilitation of the fourth goal, which includes ensuring equal quality education and promoting lifelong learning opportunities. To promote sustainability in elite sports in Iraq while breaking the cycle of the current system, it is crucial to focus on the essential social processes and basic and advanced stabilization measures. This will help establish a stable framework for elite sports in Iraq, providing positive internal and external functions.Originality: The innovation of this article focuses on the role of championship sports in achieving the United Nations Sustainable Development Goals.